Morfofunkcional'nye pokazateli vysokokvalificirovannych tchekvondisto - Kashkarov, V. A.; Vishnyakov, A. V.; Frolova, T. S. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
Managing the training process taking into consideration only the assessment and the figure of the training and competitive activity is methodologically incorrect. The management will be more precise and the assessment of the athlete's condition will be more objective if all the levels of the model are taken into account. The article deals with the results of the research into elite taekwondo athlete's morphofunctional parameters based on the results of three Olympic training cycles. The statistic processing of the data allowed to find out optimal morphofunctional parameters, which can help to achieve higher results in taekwondo. Besides, there was defined the interconnection between morphological and functional parameters. The results can be used as a basis for developing model characteristics of successful taekwondo-sportsmen.